Inhibitory effects of gallic acid in colon cancer cells - Subramanian, Aruna Priyadharshni (2016)
Colorectal cancer is a malignant tumor arising from the inner wall of the large intestine, which is the third most common type of cancer. American Cancer Society estimates about 93,090 new cases and 49,700 deaths due to colorectal cancer in the United States since 2015. Diet is thought to have a major role in the etiology of colorectal cancer. Scientists explore the phenolic phytochemicals found in various food substances for colorectal cancer treatment and prevention. In this research, a dietderived phenolic compound Gallic Acid (GA) was explored for its antiproliferative action against the colon cancer cell line HCT-15. MTT assay results illustrated that GA has an inhibitory effect on HCT-15 with IC50 value of 740 μmol/L. A timedependent inhibition of colony formation was evident with GA treatment as the maximum number of colonies formed was about 110 after 48 h. Cell cycle arrest was evident from the accumulation of GA treated HCT-15 cells at sub-G1 phase (0.98±1.03 vs 58.01±2.05) with increasing exposure time. Flow cytometric analysis of GA treated HCT-15 cells depicted various events associated with apoptosis like lipid layer breakage and reduction in mitochondrial membrane potential apart from an increase in the generation of ROS, which were in a time dependent manner. SEM and photomicrograph images of the GA-treated cells displayed membrane blebbing and cell shrinking characteristics of apoptosis. Further, the Yo-Pro-1 staining of GA treated cells confirmed apoptosis in a time dependent manner. These results propel the role of GA as a putative agent in colon cancer treatment. However, further experiments in preclinical and clinical settings are required to promote GA as a likely candidate for chemotherapy of colon cancer.